Nutritional psychiatry: Towards improving mental health by what you eat - Adan, Roger A.H.; van der Beek, Eline M.; Buitelaar, Jan K.; Cryan, John F.; Hebebrand, Johannes; Higgs, Suzanne; Schellekens, Harriet; Dickson, Suzanne L. (European neuropsychopharmacology, 2019)
Does it matter what we eat for our mental health? Accumulating data suggests that this may indeed be the case and that diet and nutrition are not only critical for human physiology and body composition, but also have significant effects on mood and mental wellbeing. While the determining factors of mental health are complex, increasing evidence indicates a strong association between a poor diet and the exacerbation of mood disorders, including anxiety and depression, as well as other neuropsychiatric conditions. There are common beliefs about the health effects of certain foods that are not supported by solid evidence and the scientific evidence demonstrating the unequivocal link between nutrition and mental health is only beginning to emerge. Current epidemiological data on nutrition and mental health do not provide information about causality or underlying mechanisms. Future studies should focus on elucidating mechanism. Randomized controlled trials should be of high quality, adequately powered and geared towards the advancement of knowledge from population-based observations towards personalized nutrition. Here, we provide an overview of the emerging field of nutritional psychiatry, exploring the scientific evidence exemplifying the importance of a well-balanced diet for mental health. We conclude that an experimental medicine approach and a mechanistic understanding is required to provide solid evidence on which future policies on diet and nutrition for mental health can be based. •Epidemiological data highlight the association between nutrition and mental health but do not provide information about causality or underlying mechanism.•Emerging findings from intervention studies suggest that diet (often combined with lifestyle) modification has potential in the prevention and treatment of mental health and may modify drug treatment effects.•Dietary intervention studies are informative but often limited methodologically due to: heterogeneity in population characteristics, lack of biomarkers to adequately stratify within and across populations, small sample sizes, lack of blinding of participants to treatment allocation and/or lack of blinded observers.•Progress will require mechanistic insight into the impact of different diets and dietary components at various levels: metabolic and cellular processes, neural circuits, core cognitive and emotional processes, whole organism and disease (models).•Genetic background can be used to strengthen hypotheses on the effects of specific nutrients on mental disorders, which can subsequently be tested in randomized controlled trials.•High quality and adequately powered experimental medicine studies will enable the identification of interventions that have a higher probability of succeeding when tested in large randomized controlled trials.•Sensitivity to mental health issues vary across the lifespan and between individuals and is influenced by genetic background, cultural setting and the environment. Nutritional needs also differ across the lifespan. To provide dietary recommendations for improving mental health, a major challenge is to advance knowledge from population-based observations towards personalized nutrition.